IMPROVEMENT OF KNOWLEDGE OF STUDENTS OF MA'ARIF VOCATIONAL SCHOOL ON WOMEN'S REPRODUCTIVE HEALTH THROUGH HEALTH PROMOTION - Kusuma Wijaya Ridi Putra; Muchamad Indra Ardian; Gerina Dwi Agustina; Anik Amila; Febriany Carla Prameswary; Roghodatul Aisy; Vivi Oktavia (Institute for Research and Community Service, Health Polytechnic of Kerta Cendekia, Sidoarjo, 2019)
Improvement of knowledge of students at Ma'arif Vocational School regarding women's reproductive health through health promotion is one form of education in the form of counseling aimed at fostering and improving healthy behavior in young women, especially in recognizing women's reproductive health. Implementation of these activities on November 24, 2018 took place at Ma'arif Vocational School, Ngaban Road, Tanggulangin, Sidoarjo. With the goal is students of Ma'arif Vocational School, Ngaban Road, Tanggulangin, Sidoarjo. Before the implementation of these activities, there is a process of preparing activities for 3 weeks before the activities are carried out, starting from the selection of health counseling materials to the submission of permits to related parties. As an evaluation, the activity was attended by 40 students and 1 teacher, the participants participated in the activity with enthusiasm and conduciveness, the activities could be carried out on time smoothly. Keywords: Women reproduction, health promotion, student of vocational school.